A Study of GAAP, IFRS &; Indian Accounting Standard: A Comprehensive Study: An Analysis of GAAP, IFRS and Indian Accounting Standards: Implications for Business Education and Adoption (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Institute of Chartered Accountants of India (ICAI) declared its proposal to introduce IFRS in India with effect from 1 April 2011. Guidelines would have a huge effect on capital markets, but scholars and stakeholders know very little about these criteria. Several countries in Europe have already switched to IFRS since 2005. They are aware of India along with IFRS in the student curriculum. Understanding the Indian Commonly Agreed Accounting Principles (GAAP) and IFRS criteria is an essential necessity individual generation. Consequently, by researching the understanding of IFRS within Indian business undergraduates, the objectives of this research is to provide a comprehensive analysis to assess the level of preparation and implementation of accounting standards. It also assist management educational institutions in their decision-making on the adoption of IFRS in the Indian Accounting Curriculum. According to the empirical results of the analysis, the implementation of GAAP, IFRS and IND AS depends mainly on the need and interest to understand the topic.